Where is Kyra? [videorecording (DVD)] - Pfeiffer, Michelle, 1957-; Sutherland, Kiefer, 1966-; Shepherd, Suzanne (Universal Studios Home Entertainment, 2018)
Kyra Johnson, a middle-aged divorcee, moves into her elderly mother's Brooklyn apartment while she looks for work and tries to get back on her feet. When her mother dies suddenly, Kyra is left without any support, both emotional and financial, and finds herself with very few options. Kyra can't accept that her once-tidy life has completely fallen apart. This leads her on a risky path of self-destruction that has devastating consequences.